Effective Mechanical Responses of a Class of 2D Chiral Materials. Issue 10 (9th October 2020) - Wang, Yun-Che; Ko, Tsai-Wen; Ren, Xuejun
Abstract : Doubly chiral material, a class of hierarchical materials, expands laterally under horizontal straining in tension when its left and bottom edge are rollers, indicating that its effective Poisson's ratio is negative; see article number 2000277 by Yun‐Che Wang and co‐workers. The lateral deformation of the top stress‐free surface is nonuniform due to couplings between tension and bending deformation modes. Large Mises stress (red) occurs in sigmoidal‐shape linking ligaments, except for their midpoint, and near the intersections between the ligaments and circular units. Most of the solid phase, including what is inside the circular regions, is under less stress (blue). Chiral materials may be ideal sensors in certain applications.